2018
DOI: 10.3889/oamjms.2018.259
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphism of CYP2A6 and Its Relationship with Nicotine Metabolism in Male Bataknese Smokers Suffered from Lung Cancer in Indonesia

Abstract: BACKGROUND:Cytochrome P450 2A6 (CYP2A6) is known as an enzyme which is responsible for the metabolism of chemical compounds.AIM:This study aimed to analyse the relationship between CYP2A6 gene polymorphism with nicotine metabolism rates and lung cancer incidence among smokers of Batak ethnic group in Indonesia.METHODS:This study was a case-control study involving 140 research subjects through a purposive sampling technique from three hospitals in Medan, Indonesia. An examination of nicotine metabolism rates wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
4
13
0
Order By: Relevance
“…The histopathology image characteristic showed 87.5% of adenocarcinoma case. This is also the same as a result shown in Soeroso et al study in 2018 that found 92.9% of adenocarcinoma type cases [10], [11].…”
Section: Discussionsupporting
confidence: 90%
“…The histopathology image characteristic showed 87.5% of adenocarcinoma case. This is also the same as a result shown in Soeroso et al study in 2018 that found 92.9% of adenocarcinoma type cases [10], [11].…”
Section: Discussionsupporting
confidence: 90%
“…This study found that the most common type of lung cancer found in Batak tribe in Indonesia was adenocarcinoma (92.9%), and the most consumed cigarette type was clove cigarettes. Clove cigarettes contain clove that will make smokers suck in more deeply; thus, smokes containing carcinogenic substances eventually enter the peripheral respiratory tract [ 16 ], [ 18 ]. Syahruddin et al, [ 19 ] found that the EGFR mutations rate among Indonesian population reached 57.1% common mutations (exon 19 ins/dels, L858r) and about 29% uncommon mutations (G719X, exon 20 ins, T790M, L861Q).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, it has been recognized that differences in the activity of enzymes involved in nicotine metabolism are partly responsible for inter-individual variation in lung cancer risk among smokers [32,33,34,35]. CYP2A6 is a principal enzyme in nicotine metabolism, and CYP2A6-mediated C-oxidase activity has been reported to correlate with exposure to carcinogens by smoking [32,33,34,35]. Many reports have demonstrated that CYP2A6 variants that exert reduced enzymatic activity are associated with lower lung cancer risk [32,33,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…CYP2A6 is a principal enzyme in nicotine metabolism, and CYP2A6-mediated C-oxidase activity has been reported to correlate with exposure to carcinogens by smoking [32,33,34,35]. Many reports have demonstrated that CYP2A6 variants that exert reduced enzymatic activity are associated with lower lung cancer risk [32,33,34,35]. However, these genetic polymorphisms are reported to account for only a portion of the variation in CYP2A6 activity [4].…”
Section: Discussionmentioning
confidence: 99%